Ajaran Satya dan Dharma dalam Membentuk Karakter Keluarga Hindu di Desa Peguyangan Kangin Kota Denpasar - I Ketut Sudarsana (JSSH (Jurnal Sains Sosial dan Humaniora), 2018)
This research is derived from the background that today is age of kali yuga, which signed by decreasing of moral and ethic from most human beings on earth. On such situation, man will lose its steps, that are, humanity values on its self since born. On this Kali Age, men are controlled passion, lose love, suspect each other, even there are tendencies to do bad things represent today trend. Corruption everywhere, there are no fear or shame to make sin, giving sign that the truth is fade away. Fighting among tribes and kill each other happened in tremendous, love is gone to humans. Progress in science and technology has give great benefits to mankind, because all easier has been given. In other side if the progress of science and technology will be misused, it will be very dangerous not only to mankind but have impact to all creatures.